PENERAPAN KEPALA SEKOLAH SEBAGAI SUPEVISOR AKADEMIK DALAM MENINGKATKAN KINERJA GURU DI KABUPATEN WAJO - Sumarni, Sumarni (Pascasarjana Universitas Negeri Makassar, 2017)
This research aims to know the role of the head of school as an academic supervisor in improving the performance of the teacher in Tempe, Wajo Kabutaen 200 SDN. This research is quantitative descriptive research. The population in this study all existing master class in SDN 200 Tempe Wajo Regency as many as 12 people. Sampling Sampling technique of research with saturated, is a technique to determine the sample when all members of a population is used as a sample. Research instrument in the form of the now, interview, danobservasi. The research found the principal role as academic supervisor was further intensified and improved performance on increasing teacher SDN 200 Tempe Tempeh subdistrict of Wajo Regency. Reverse when the less intensive implementation roles the head of the school as academic supervisor, then increasingly did not develop performance teacher at SDN 200 Tempe, Tempe, Wajo Regency Subdistrict. Furthermore when r count should be referred to the table value r, retrieved r count categorized qualitatively on the extent the very strong correlation between 0.800 – 1.000. Finally, it is recommended to all heads of school as an academic supervisor at SDN 200 Tempe Tempeh subdistrict of Wajo Regency further enhance its role in the future, so that the citizens of the school and school Committee (community and parents of students) more concerned and actively participate in an effort to improve the quality of education.